2008
DOI: 10.1007/s10531-008-9394-4
|View full text |Cite
|
Sign up to set email alerts
|

The white-backed woodpecker: umbrella species for forest conservation planning?

Abstract: In northern Europe, a long history of land use has led to profound changes within forest ecosystems. The white-backed woodpecker (Dendrocopos leucotos) is one of several specialised forest species whose populations have declined. Conservation management directed at this species' habitat has made it a de facto umbrella species for conservation of the biodiversity associated with forests rich in deciduous trees and dead wood. We assessed empirically the value of the white-backed woodpecker as an indicator and um… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 46 publications
2
68
0
4
Order By: Relevance
“…For example, some authors have found surrogates to be ineffective in small areas (Caro et al 2004), but effective in larger areas if minimum representation of the surrogate was met (Garson et al 2002). Effectiveness as a surrogate may also vary across background taxa (Roberge et al 2008). In a comprehensive review of 575 surrogacy tests from 19 studies, Rodrigues and Brooks (2007) evaluated the effectiveness of protected areas designed using surrogate species data for representing target taxa and found a positive but weak surrogacy effect.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some authors have found surrogates to be ineffective in small areas (Caro et al 2004), but effective in larger areas if minimum representation of the surrogate was met (Garson et al 2002). Effectiveness as a surrogate may also vary across background taxa (Roberge et al 2008). In a comprehensive review of 575 surrogacy tests from 19 studies, Rodrigues and Brooks (2007) evaluated the effectiveness of protected areas designed using surrogate species data for representing target taxa and found a positive but weak surrogacy effect.…”
Section: Discussionmentioning
confidence: 99%
“…Continuing land use changes and deforestation may threaten small populations of woodpeckers living in this region. In this way, protected areas located along the Andes mountain range, such as the Conguillío National Park, may fail to conserve Magellanic Woodpeckers and potentially other forest biota, given that woodpeckers are closely associated with many other forest specialists (Garmendia et al 2006, Roberge et al 2008b. Further studies should address how accelerating land-use change from agricultural intensification, forestry, exotic plantations, and urbanization around the southern Chile national parks may contribute to declines of Magellanic Woodpeckers, as has been assessed for other woodpecker species (e.g., see Gjerde et al 2005, Roberge et al 2008a.…”
Section: Discussionmentioning
confidence: 99%
“…In intensively used systems, such as production forests and hydroelectric rivers, restoration is restricted because of the difficulties in combining production with restoration measures. Forest landscapes include examples of restoration activities to reintroduce functional and structural heterogeneity, in some cases triggered by attempts to support populations of threatened species, such as the White-backed Woodpecker (Dendrocopos leucotos) (Roberge et al 2008). In hydroelectric rivers, facilitation of fish migration is a major concern, although there are few real-world examples.…”
Section: Swedenmentioning
confidence: 99%